Utilizing cerlis model in improving creative writing skills - Nazir, Faridah; Jano, Zanariah; Omar, Norliza; Kamarudin, Norzai Shahida (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
The objectives of this paper were to identify the effectiveness of Cerlis Model in assisting teachers to improve students’ creative writing skills such as descriptive and imaginative essays and to analyze whether the model can improve students’ ways of expressing and organizing ideas in composing essays accurately. Samples consisted of 5 students from a primary school in Seremban, Negeri Sembilan. This study was conducted using a narrative qualitative approach through observation, questionnaire survey and document analysis and the results were reported using relevant tables, photos, and visual graphics. The study focused on students that lack ideas in producing creative essays such as descriptive and imaginative types. The results yielded that the Cerlis Model was able to create fun in learning and generate a high confidence level in producing ideas for essay writing. Indeed, Cerlis Model is able to increase students’ interests in writing essays and their comprehension level. This study also shows that games are generating students’ ideas for composing descriptive and imaginative essays.